KONSEP NILAI TAMBAH PADA AKUNTANSI SYARIAH - Karomah, Ummul; Latifah, Eny (JITAA : Journal Of International Taxation, Accounting And Auditing, 2023)
Research using qualitative methods of this type of literature has the aim of knowing the concept of added value in Islamic accounting. The results showed that added value in Sharia accounting refers to the value added to the economic, mental, and spiritual performance of an entity, which is halal and distributed in accordance with the law. Added value is not just profit but also has a deeper meaning in the distribution of resources to all stakeholders. A value-added statement is financial reporting that shows the added value created and distributed by a company. Value-added statements are in line with Islam especially in terms of fairness. Value added in accounting refers to the value added to the product by the company.